"It was a joke:" Patterns in girls' and boys' self-reported motivations for digital dating abuse behaviors. (March 2021) - Reed, Lauren A.; Lawler, Siobhan M.; Cosgrove, Jenny McCullough; Tolman, Richard M.; Ward, L. Monique
Highlights: A sample of 703 high school students with dating experience were surveyed. Multiple methods explored motivations to engage in digital dating abuse behaviors. Frequent motivations included joking and being upset, angry, and in a fight. Data pattern analysis showed motivations differed by type of behavior and gender. It was a joke was a common motivation that was difficult to interpret. Abstract: Digital dating abuse (DDA) is a pattern of behaviors using mobile phones and social media to harass, pressure, coerce, and threaten a dating partner. Little is known about teen girls' and boys' motivations to perpetrate digital dating abuse. This study drew from survey research with 703 high school students and used multiple methods to explore DDA motivations. Quantitative analyses found that frequent motivations for DDA behaviors included it was a joke, I was upset, I was angry, and we were in a fight . Few gender differences were found. Qualitative data pattern analysis provided additional context to DDA motivation responses. Patterns of DDA motivations differed depending on the type of DDA behavior. When participants reported multiple motivations for a behavior, there was some common clustering of motivations across participants. It was a joke was indeed a common motivation for some DDA behaviors, but participants often reported multiple motivations, which made these responses more difficult to interpret. Sexual DDA behaviors were particularly gendered. These results have important implications for our understanding of DDA perpetration among teens and future DDA assessment and measurement.